DEVELOPMENT OF RELATIONS WITH CHILD STIMULATING CHILDREN IN PUBLIC HEALTH CENTER SAWAH LEBAR BENGKULU CITY - Yeni Eliyanti (Jurnal Vokasi Keperawatan (JVK), 2020)
Measures to provide stimulation done on the principle that the stimulation is an expression of love and affection, play with the kids, very happy together, do stimulation in gradual and sustained, and includes four areas of developing capability. The problem in this research is still the number of infants whose development has not been in accordance with his age. The purpose of the study was to determine the relationship of maternal stimulation with the development of children under five in Public Health Center Sawah Lebar Bengkulu City.This type of research is cross sectional. A population of 1.642 people and sampling with simple random sampling as many as 94 people. Data used in the study is the use of primary and secondary data. Analysis of the data in this study using univariate and bivariate data analysis with chi-square statistic methods at significance level of 0.05. The results of this study are almost half of children under 30 (31.9%) whose mothers are less active stimulation, a fraction toddlers 4 (4.3%) that the child's development there may be irregularities and statistical test results obtained ? = 0.000 (? ? ? 0.05), it indicates that there is a relationship stimulation mothers with toddlers in Public Health Center Sawah Lebar Bengkulu City.This study is expected to be input or information to improve parenting with adequate stimulation is also to improve the development of children, especially for health workers and child nursing profession.